Relationship between Business IT Alignment and Risk Management on Company Performance: A Systematic Literature Review - Wardhani, Zahrin Nurshofia; Sholiq, Sholiq (ILKOMNIKA, 2025)
Continuous change is an important thing that must be faced by a company. Such as the increasing integration of information technology (IT) in business operations that has led corporate executives to review the importance of aligning IT and business strategies. At the same time, effective risk management has become critical to ensuring organizational resilience and performance. So this systematic literature review aims to find out more about the relationship between IT-Business strategy alignment and risk management on company performance. The literature review was conducted by sorting and reviewing existing research from publications between 2014 and 2025 by looking at Q1 and Q2 quartiles and using the 5W1H analysis method. This review identified a thorough understanding of Business IT Alignment and Risk Management. This literature review shows that the alignment of IT and business strategies, along with effective risk management, plays an important role in improving corporate performance. The research reveals that the integration of these two factors enables companies to be more efficient, innovative and prepared for market uncertainty.